The Effect Of Learning Media Management And Self-Motivation On Science Literacy Ability - Hidayati, Suci; Istiana, Lailatul; Karim, Abdul Malik (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The basis of this paper is the teacher's ability to manage the learning media used during learning because it is an important component in delivering teaching materials. Learning objectives can be effectively achieved if teachers can manage the media needs of each teaching material and use it appropriately. The post-pandemic learning process is felt to be less meaningful and tends to be boring for students, so teachers must be able to innovate in choosing and creating learning media that can motivate students to learn. This study aims to determine the benefits and effects of using